Understanding extreme-wave hazards on high-energy coasts requires a standardised approach to field data collection: analysis and recommendations - Cox, Rónadh; Bourke, Mary C.; Engel, Max; Kennedy, Andrew B.; Lau, Annie; Suanez, Serge; Boulton, Sarah J.; Oliveira, Maria Alexandra; Paris, Raphaël; Salmanidou, Dimitra; Spiske, Michaela; Stephenson, Wayne; et al. (EGUsphere, 2025)
Abstract: Coastal boulder deposits provide vital information on extreme wave events. They are crucial for understanding storm and tsunami impacts on rocky coasts, and for understanding long-term hazard histories. But study of these deposits is still a young field, and growth in investigation has been rapid, without much contact between research groups. Therefore, inconsistencies in field data collection among different studies hinder cross-site comparisons and limit the applicability of findings across disciplines. This paper analyses field methodologies for coastal boulder deposit measurement based using an integrated database (ISROC-DB), demonstrating inconsistencies in current approaches. We use the analysis as a basis for outlining protocols to improve data comparability and utility for geoscientists, engineers, and coastal planners. Using a standardised and comprehensive set of measurements, with due attention to precision and reproducibility, will help ensure complete data retrieval in the field. Applying these approaches will further ensure that data collected at different times and/or locations, and by different groups, is useful not just for the study being undertaken, but for other researchers to analyse and reuse. This is fosters development of the large, internally consistent datasets that are the basis for fruitful meta-analysis; and is particularly timely given increasing focus on longitudinal monitoring of coastal change. By recommending a common set of measurements, adaptable to available equipment and personnel, this work aims to support accurate and thorough coastal boulder deposit documentation, enabling broader applicability and future-proofed datasets. Field protocols described and recommended here also apply as best practices for coastal geomorphology field work in general.
Gesehen am 02.07.2025